DECENNIAL CELEBRATIONS OF REPUBLIC: ZONGULDAK EXAMPLE - Hasan KARAKUZU (Fırat University, 2019)
Turkish nation that won the existence fight through Turkish War of Independence brings this fight to the next stage under the leadership of Mustafa Kemal and establishes the Republic of Turkey. Acceptance of political regime as the Republic on 29 October 1923 is widely recognized by Turkish people. The most important indicator of this situation is that Turkish people actively have participated and been interested in the 29 October Republic Day Celebrations from 1924. This Turkish nation’s enthusiasm is also the assurance of future of the young Republic. At the same time, this minimizes the concerns about the future of young Turkey. Thus, Turkish people celebrate the Republic Day bodily together. Especially, the special attention is paid to the decennial celebrations of Republic in order to show that there is not any regime problem in Turkey. The preparations, started at the governmental stage, are planned down to the last detail from province, district to the towns and villages. It is strived in order that the celebrations are made without any problem and in an order. In our this paper, the applications of decennial celebrations of Republic, which become the symbol of proving the legality of new regime in Zonguldak and its districts, are discussed. Furthermore, as the subject is examined, it is tried to show the reflections of reactions by people during the celebrations.